The GlucoseGoddess method - Inchauspé, Jessie (Simon Element, an imprint of Simon & Schuster, Inc., 2023)
"Jessie Inchauspé offers a framework for healing through science-backed nutrition hacks with this four-week program incorporating the principles of how to avoid glucose spikes into your everyday life"--